Daulah Umayyah di Andalusia dan Pengaruhnya Terhadap Kebangkitan Bangsa Eropa - Iqbal Iqbal (Universitas Islam Negeri Alauddin Makassar, 2015)
This paper explains about Umayyah’s empire in Andalusia specially about his influence to western’s civilization. Before they became to super power countries, actually they were rearward state. When Islam was coming to Andalusia, Moslems built so much civilization. It’s like Cordova University had become to the Central of Science in Europe. So many Students were studying in there until Umayyah’s empire had fallen. Islam was coming in Andalusia when Musa Ibn Nushair became an Islamic governor in North Africa. At the same time in Andalusia was chaos by Gothic Kingdom. So, people of Andalusia asked some help to Islamic empire in North Africa. Finally, Musa Ibn Nushair sent Thariq Ibn Ziyad to help Andalusia’s people. It’s beginning of Moslems were coming to Andalusia. After Umayyah’s empire in Damaskus had Fallen, Abdul Rahman al-Dakhil rebuilt Umayyah’s empire in Andalusia. So much Influence after this, for example in philosophy field had Ibn Rusyd as famous philosopher. Ibn Rusyd thought was very influence to Andalusia’s people until Andalusia’s people made renaissance on 14th. Although Umayyah’s empire had lost, but spirit science of Umayyah’s empire still exist in Europe. This paper explain on history side and doing on qualitative research by library research.